Geography Teachers' Pedagogical Content Knowledge: A Systematic Review - Smit, Eefje; Tuithof, Hanneke; Savelsbergh, Elwin; Béneker, Tine (Journal of geography (Houston), 2023)
Pedagogical Content Knowledge (PCK) is the knowledge teachers use to teach a specific subject to a specific audience. The importance of PCK to quality teaching is widely recognized. However, an overview of research about geography teachers' PCK is missing. To fill this gap, we conducted a systematic review. We analyzed 43 empirical studies, but only 9 used PCK as a framework. Most studies addressed instructional strategies or teaching orientations. The studies were too diverse to draw conclusions on geography teachers' PCK in general. But portraits of 16 geography teachers emphasized the necessity of geographical knowledge and teaching experience for PCK-quality.